2009
DOI: 10.3846/1648-4142.2009.24.187-191
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Motor Characteristics of D‐rme‐e Fuel Blend During On‐field Tests

Abstract: Abstract.A detailed analysis of the characteristics of D-RME-E (diesel-rapeseed methyl ester-ethanol) was carefully performed fuelling an 18 kW capacity tractor unit equipped with the four-stroke D21A1 diesel engine (combustion chamber consists of a dished piston). Th e conducted on-fi eld test demonstrated a positive eff ect on the dynamic and ecological characteristics of the tractor unit while fuelling the engine with biodiesel blend 70% D+30% RME (hereinaft er -B30) admixed with dehydrated ethanol additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Bridgwater and Canales (2013) found that density of ternary mixtures containing 50 wt% of ethanol started to increase in the bottom layers, when the share of pyrolytic oil was increased, while the maximum value of that parameter was reached for sample composed of 50 wt% of ethanol, 30 wt% pyrolytic oil and 20 wt% of biodiesel. In turn, Raslavičius and Bazaras (2009), analysing the effect of addition of 5 and 10% of ethanol to blend consisting of 70% of diesel oil and 30% of rapeseed methyl ester, found that in case of 5% addition of alcohol the exploitation characteristics of the tractor unit were analogous within the total range of loads as operating on pure mineral diesel. Due to this fact authors suggested that sample with a lower addition of ethanol could be used in the areas especially sensitive to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Bridgwater and Canales (2013) found that density of ternary mixtures containing 50 wt% of ethanol started to increase in the bottom layers, when the share of pyrolytic oil was increased, while the maximum value of that parameter was reached for sample composed of 50 wt% of ethanol, 30 wt% pyrolytic oil and 20 wt% of biodiesel. In turn, Raslavičius and Bazaras (2009), analysing the effect of addition of 5 and 10% of ethanol to blend consisting of 70% of diesel oil and 30% of rapeseed methyl ester, found that in case of 5% addition of alcohol the exploitation characteristics of the tractor unit were analogous within the total range of loads as operating on pure mineral diesel. Due to this fact authors suggested that sample with a lower addition of ethanol could be used in the areas especially sensitive to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Producing and using biofuels has opened a new area in Lithuania as well as researches in this area (Matijošius and Sokolovskij 2009;Pukalskas et al 2009;Raslavičius and Bazaras 2009;Lebedevas and Lebedeva 2009;Pukalskas 2008a and2008b;Butkus et al 2007; Lebedevas et al 2007;Raslavičius and Markšaitis 2007;Lebedevas et al 2006aLebedevas et al , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…Th e expansion of production and the use of biofuels are determined by the legal acts of the European Commission and National legal acts encouraging such production and usage Producing and using biofuels has opened a new area in Lithuania as well as researches in this area (Matijošius and Sokolovskij 2009;Raslavičius and Bazaras 2009;Raslavičius 2009;Bazaras and Raslavičius 2008;Lebedevas and Lebedeva 2009;Pukalskas 2008a and2008b;Lebedevas et al 2007a and2007b;Raslavičius and Markšaitis 2007;Labeckas 2005;Makarevičienė 2005). …”
Section: Introductionmentioning
confidence: 99%